Temperature independent low loss dielectrics based on quaternary pyrochlore oxides. (June 2018) - Giampaoli, Gabriella; Siritanon, Theeranun; Day, Blake; Li, Jun; Subramanian, M.A.
Abstract: Quaternary pyrochlore phases of the general formula Bi2- x Ca x M 2- y M' y O7- x /2+ y /2 ( M = Ti, Hf, Sn; M' = Sb, Nb, Ta) were prepared by solid state reactions and characterized via structural and dielectric properties. The cubic a -lattice parameters show an expected linear relationship with the ionic radii of the substituted M cations. The solid solution Bi2- x Ca x Sn2- y Sb y O7- x /2+ y /2 was analyzed by X-ray and neutron diffractions. The solubility limit is close to x = 1.3, and for x > 1.3, the reaction products contain a mixture of the pyrochlore phase and the Ca2 Sb2 O7 weberite phase. The refined formulas for compositions with nominal calcium content x = 0.5, 1.0, and 1.5 are Bi1.36 Ca0.64 Sn1.60 Sb0.40 O6.88, Bi0.82 Ca1.18 Sn1.10 Sb0.90 O6.86, and Bi0.76 Ca1.24 Sn1.06 Sb0.94 O6.85 respectively, indicating slight oxygen deficiencies. Temperature and frequency independent dielectric constants and low loss are observed at 1 MHz. The dielectric constants vary from 16 to 98 depending on the composition. We have also prepared new cubic quaternary pyrochlores with the formula BiCd M TeO7, where M = Al, Cr, Ga, In, Fe, Mn, and Sc. Magnetic property measurement shows paramagnetism in the M = Cr and Mn phases but antiferromagnetism with short-range correlations in the M = Fe phase. All these compositions are insulating. The measured dielectric constants and dielectric loss are independent of temperature and frequency. Graphical abstract: Image 1